Penerapan Fungsi Validasi Topologi untuk Penentuan Batas Desa Mengikuti Permendagri No 45 Tahun 2016 - Mursyid, Farhan; Yulfa, Arie (YASIN, 2024)
The objectives of this research are: 1) to know the topology validation function, 2) to know the use of topology rules such as polygon, polyline and point rules according to Permendagri No. 45/2016, 3) to make it easier for the government/other researchers to validate the topology of administrative boundaries. This type of research is quantitative with geospatial analysis, research can be done topology checking using ArcGIS software where there are topology validation tools to identify errors contained in the data. The results of the research found that polyline topology validation only found errors in 2 object features, namely Must Not Overlap with 6 errors and Must Not Have Dangels with 1 error. Validation of polygon topology has no errors, it is just detected outside the area so an exception is made. Validation of point topology that has errors is only found in 2 feature objects, namely Point Must Be Covered By Line with 2 errors, and Must Be Disjoint with 41 errors.